1989
DOI: 10.1038/bjc.1989.99
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation in mortality from leukaemia and other cancers in England and Wales in relation to proximity to nuclear installations, 1969-78

Abstract: Summary The distribution of mortality from 11 causes of death (lymphoid leukaemia, other Reports of an increased incidence of leukaemia in young people in the vicinity of certain nuclear installations have caused concern about the possible effect on communities that live near other such installations. The extent and localisation of the increase near Sellafield leaves no doubt about its reality (Gardner & Winter, 1984) but it is unclear how far many of the other reports represent selection of high rates that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(41 citation statements)
references
References 9 publications
4
36
0
1
Order By: Relevance
“…58 Clusters were sought and identified in the vicinity of other nuclear establishments in the UK and other countries, [59][60][61] although leukemia clusters were not found exclusively in the vicinity of nuclear reactors. 62 The reports of Gardner et al 63,64 however, suggested that occupational exposure of men at Sellafield might be linked to increased susceptibility to leukemia or non-Hodgkin's lymphoma in children.…”
Section: Paternal Exposure To Ionizing Radiationmentioning
confidence: 99%
“…58 Clusters were sought and identified in the vicinity of other nuclear establishments in the UK and other countries, [59][60][61] although leukemia clusters were not found exclusively in the vicinity of nuclear reactors. 62 The reports of Gardner et al 63,64 however, suggested that occupational exposure of men at Sellafield might be linked to increased susceptibility to leukemia or non-Hodgkin's lymphoma in children.…”
Section: Paternal Exposure To Ionizing Radiationmentioning
confidence: 99%
“…The validity of death-certificate diagnoses for investigating cancer is generally accepted (2,3,18,19). Except for Tarragona, none of the provinces studied are equipped with population-based cancer registries that would otherwise enable cancer incidence to be studied in these areas.…”
Section: Discussionmentioning
confidence: 99%
“…Since higher socio-economic status is a possible risk factor for lymphoproliferative disease [33][34][35], we conducted analyses with univariate Poisson models to examine the effect of the ARF factors described in Section 2.3. Frequentist, likelihood-based methods were used in this variable selection phase of the analyses since it would have been time-prohibitive to use the full Bayesian model.…”
Section: Leukaemia Risk Estimatesmentioning
confidence: 99%